Penerapan Metode Yanbu’a untuk Meningkatkan Kemampuan Santri dalam Membaca Al - Qu’ran di TPQ Daarul Muttaqiin - Masduqi, Khumaidi; Isti’anah, Isti’anah (IAINU Kebumen, 2023)
TPQ Daarul Muttaqiin is a non-formal educational institution in the field of Islamic religion in Seliling Village, which aims to provide teaching to read and write the Qur'an, as well as understand the basics of Islam in children from an early age. There are still many students who need to be improved in reading the Qur'an in accordance with the rules of tajwid science. Therefore, the use of appropriate and appropriate strategies is very important, in order to improve the ability to read the Qur'an in students from an early age. The purpose of this study was to find out how the implementation and influence of the yanbu'a method was applied at TPQ Daarul Muttaqiin Seliling village and to find out the supporting and inhibiting factors in the application of the Yanbu'a method at TPQ Daarul Muttaqiin in improving the ability of students to read the Qur'an. In this study the authors used a type of qualitative research, so the presence of researchers in the field is very important. The type of data presented in this study is qualitative data, so the data analysis used is descriptive data analysis method. The results showed that the application of the Yanbu'a method applied by the TPQ Daarul Muttaqiin institution to improve the ability to read the Koran for students, namely: 1) Learning activities started at 16.30 WIB, 2) the method used was Yanbu'a, 3) getting used to memorizing daily prayers along with their meanings and short letters, 4) getting students to follow muroja'ah, 5) learning recitation subject, 7) conducting learning evaluations for students. The obstacles faced by the TPQ Daarul Muttaqiin institution in improving the ability to read the Koran are classified into two, namely internal factors and external factors. Solutions to overcome the obstacles encountered, in accordance with institutional policies based on deliberative agreements carried out by institutional administrators and the teacher council.